Neuro-education The Myths and Realities - Mondal, Kuheli; K. (JOURNAL OF INDIAN EDUCATION, 2017)
Neuro-education being a relatively new discipline is faced with many obstacles, which are termed as ‘neuromyths’ in the teaching-learning practice. The present paper speaks about the prevalence of neuromyths in the minds of teachers and educationists. It mainly deals with the myths, which act as a hindrance in the effective functioning of the education system, and how these are said to be discarded by different researchers to be just named as neuromyths and not reality. Hence, it can be concluded that neuromyths are superfluous, which create misconceptions.